Consolidation electrochemotherapy with bleomycin in metastatic melanoma during treatment with dabrafenib - Valpione Sara; Campana Luca G.; Pigozzo Jacopo; Chiarion-Sileni Vanna (Radiology and Oncology, 2015)
Background. Small molecules that inhibit V600 mutated BRAF protein, such as vemurafenib and dabrafenib, are effective in treatment of metastatic melanoma.